Relationship on the performance of doctors in inpatients towards the level of patient satisfaction. - Samodra, Ilham Daud; Prijambodo, Tjatur; Ghufron, Musa; Widyaningsih, Sri (Gaceta Médica de Caracas, 2021)
Introduction: The hospital is one place that provides personal health services in the short term and long term. Assessing a hospital’s quality of service can be seen from the satisfaction of patients who seek treatment. This study aimed to determine inpatient clinic patients’ characteristics and the relationship between doctors’ performance and satisfaction levels of inpatients.